Caracterização molecular de três espécies de Trachycephalus (Anura: Hylidae): investigando potenciais híbridos interespecíficos - Zaidan, Fernanda Couto (2014)
Hybrids are evolutionary units generally without clear morphological, behavioral and genetic delimitation, thus representing a challenge to taxonomy and systematics. They can morphologically resemble their parents or, due to introgression, their characteristics can be diluted with a prevailing appearance of one of the parental species, which could hinder identification. One way to identify hybrids is through molecular biology tools, such as mitochondrial DNA (maternal inherintance exclusively) and nuclear DNA (maternal and paternal inheritance), allowing genetic comparisons. Besides hybridization, conflicting mtDNA and nDNA identifications may have other explanations, such as Incomplete Lineage Sorting. Some individuals collected in localities of Espírito Santo State, Brazil, presented a mix of morphological characters of T. mesophaeus and T. nigromaculatus, which are the only Trachycephalus species known to the region. However, previous studies using COI sequences grouped theses individuals as T. typhonius. Giving this, we sequenced fragments of two mitochondrial genes (COI and ND2) and part of the nuclear exon of tyrosinase of 173 individuals of Trachycephalus, in order to better clarify the taxonomic uncertainty, and the link between morphological and genetic characters behind the identifications, according to the occurrence area. Results of molecular phylogenies, genetic divergences, haplotype networks, and single nucleotide polymorphisms (SNPs) confirmed .T. mesophaeus, T. nigromaculatus, and T. typhonius as distinct evolutionary lineages and revealed seven more individuals potentially hybrids, but morphologically assigned to one species. Due to the slow mutation rate of tyrosinase, the most recently diverged species (T. typhonius and T. nigromaculatus) have not completely sorted in this gene. Trachycephalus mesophaeus is the oldest species of the three, and it was identified unambiguously in all analysis. Here, for the first time, evidence of bidirectional introgression between T. nigromaculatus and T. typhonius and between T. nigromaculatus and T. mesophaeus, with signs of F1 individuals, is presented. The use of ND2 gene seems to be more efficient than COI to recover the phylogenies in this particular group and, although tyrosinase is a slow evolving gene, it contributed significantly in order to identify cytonuclear incongruences. Our results indicate a complex phylogenetic history of Trachycephalus, and that more introgressive hybrids may be identified with the use of faster nuclear markers and the inclusion of more species of the genus in the analyses..